Between structure and agency: the use of conditional welfare through the lens of social capital. Issue 2 (15th March 2023) - Scalise, Gemma
ABSTRACT: This article assumes that the theory of social capital can contribute to explaining some of the processes behind decision-making independence and the informal aspects of relationship in the implementation of social policies. To support this theoretical proposition by means of case-based empirical evidence, the article focuses on the implementation of the principle of welfare conditionality, which links the access to income support benefits on the acceptance of job search activities and training. Three comparative cases show that its implementation varies significantly in the different contexts: conditionality embodies a very weak principle in Barcelona, which is not applied in practice; in Lyon it has a symbolic function representing a formality that provides access to an unconditional right; in Gothenburg it is implemented as a stringent and effective proof of activation. Among the many institutional and structural factors that help explain these differences, the article shows that there are also specific forms of trust, group identity and mutual recognition that motivate civil servants' agency and discretionary choices.